Load Transfer Characteristics of a Cable Bolt in DEPT - Xuwei Li (Shock and Vibration)
Cable bolts help surrounding rock masses of underground excavations to form internal rock structure and thus self-stabilize through effective load transfer between rock masses and cable bolts. The load transfer characteristics of cable bolt play the most significant role in cable selection for support design. There are many factors potentially affecting the load transfer characteristics of cable bolt via strengthening or weakening load contributors such as cable bonding, mechanical interlocking, frictional resistance at cable-grout interface and grout-rock interface, and shearing of grout anchorage. Double embedment pull test (DEPT) is an effective, reliable, and repeatable test method of investigating the load transfer characteristics of cable bolt and thus was selected in this study. With DEPT, the influence of factors such as cable rotation, grout age, grout anchorage annulus thickness, cable wire profile, and failure mode on the load transfer characteristics of cable bolt were investigated in terms of tensile strength and stiffness in different loading stages. Conclusions drawn from the study can be used to improve cable installation quality and to select appropriate cable bolting technique.